Hermeneutical and analytical jurisprudence - Spaić Bojan (Anali Pravnog Fakulteta u Beogradu)
The article examines the main strands of development in jurisprudence in the last few decades from the standpoint of the metatheoretical differentiation between analytical and hermeneutical perspective in the study of law. The author claims that recent jurisprudent accounts can rarely be positioned within the traditional dichotomy natural law theories - legal positivism, and that this dichotomy is not able to account for the differences between contemporary conceptions of law. As an alternative the difference between the analytical and hermeneutical traditions in philosophy are explained, as they have crucially influenced posthartian strands in Anglo-American philosophy and postkelsenian strands in continental philosophy of law. Finally, the influence of hermeneutical philosophy and legal theory is examined in regards of the development of a hermeneutical theory of law and the development of legal hermeneutics.